Inhomogeneity correction of magnetic resonance brain images - Chua, Zin Yan (2013)
Magnetic resonance imaging (MRI) is a widely used non-invasive visualization technique in medical field. The images acquired often suffer from intensity nonuniformity, or inhomogeneity, which hampers automated analysis of the images. This artifact is mainly caused by the radio frequency (RF) coil design, gradient-driven eddy currents, and acquisition pulse sequences. In this research, we are focusing on techniques to correct the intensity inhomogeneity by performing a coarse preliminary